Design and Simulation of Control Systems for Field Survey Mobile Robot Platform. - Wan Ismail, Wan Ishak; Shamshiri, Ramin (2013)
The aim of this study was to design automatic and accurate control systems for wheel speed and steering of an agricultural mobile robot. Three controllers, including lead-lag compensator, Proportional-Integral-Derivative (PID) and fuzzy logic controller were designed and simulated in this study to control the angular rate of the shaft of a DC motor actuator for a field survey mobile robot that moves between plants rows to perform image acquisition task through a digital camera mounted on a two link arm attached on the robot base. The response of the actuator model for each controller were determined and compared for a sinusoidal and a step input that simulated robot speed and positioning references respectively. Performance analysis showed the effectiveness of the PID and lead-lag compensator response for the wheel steering task, while the fuzzy logic controller design had a better performance in wheel speed control. The output of this analysis was a proved satisfaction of the proposed design criteria which results enhanced mobility of the robot in terms of fast response, speed control accuracy and smooth steering at row-end turnings.